'All the lonely people': embracing autoethnographic creative analytical practice at the 2017 World Masters Games. Issue 3 (27th May 2019) - Wright, Richard Keith
ABSTRACT: It started on Friday 21st April 2017. That was the opening day of a multi-sport event that involved 24, 905 participants, 1, 094 non-playing officials and 3, 216 volunteers. It was a day that I had been waiting for since March 2012. It was a day I spent largely by myself, surrounded by likeminded active participants and hobbyists from all over 100 different countries. This piece of autoethnographic creative analytical practice (CAP applies Clawson, M. and J. Knetsch 1966. Economics of Outdoor Recreation . Baltimore: John Hopkins) five phases of the leisure experience to the author's first twelve hours as an athlete at the 2017 World Masters Games. By bringing together my two biggest passions, amateur sport and popular music, I seek to stir up your sociological imagination, and let you see things from my unique perspective. I want you to finish this story, thinking about all the lonely people that you may have unintentionally missed/excluded from your leisure studies research.